What do older people think that others think of them, and does it matter? The role of meta-perceptions and social norms in the prediction of perceived age discrimination - Vauclair, C.-M. (2017)
Psychological theories of aging highlight the importance of social context. However, very little research has distinguished empirically between older people’s perception of how others in their social context perceive them (personal meta-perceptions) and the shared perceptions in society (societal meta-perceptions). Drawing on theories of intergroup relations and stereotyping and using a multilevel perspective, this article examines how well older people’s perceptions of age discrimination (PAD) are predicted by (a) older people’s personal meta-perceptions, (b) societal meta-perceptions, and (c) social norms of intolerance toward age prejudice. Aging meta-perceptions are differentiated into the cognitive and affective components of ageism. Multilevel analyses of data from the European Social Survey (Nover 70 years of age = 8,123, 29 countries; European Social Survey (ESS) Round 4 Data, 2008) confirmed that older people’s personal meta-perceptions of negative age stereotypes and specific intergroup emotions (pity, envy, contempt) are associated with higher PAD. However, at the societal-level, only paternalistic meta-perceptions were consistently associated with greater PAD. The results show that a few meta-perceptions operate only as a psychological phenomenon in explaining PAD, some carry consonant, and others carry contrasting effects at the societal-level of analysis. This evidence extends previous research on aging meta-perceptions by showing that both the content of meta-perceptions and the level of analysis at which they are assessed make distinct contributions to PAD. Moreover, social norms of intolerance of age prejudice have a larger statistical effect than societal meta-perceptions. Social interventions would benefit from considering these differential findings.